Detecting gastrointestinal manifestations in patients with systemic sclerosis using anti-gAChR antibodies - Shunya Nakane; Masataka Umeda; Shin-ya Kawashiri; Akihiro Mukaino; Kunihiro Ichinose; Osamu Higuchi; Yasuhiro Maeda; Hideki Nakamura; Hidenori Matsuo; Atsushi Kawakami (Arthritis Research & Therapy, 2020)
Abstract Background Patients with systemic sclerosis (SSc) complicated by gastrointestinal dysmotility are difficult to treat and have high mortality. To clarify the pathogenesis of gastrointestinal manifestations, we aimed to demonstrate the association among the clinical features of SSc, the serological markers, the autoantibodies against nicotinic acetylcholine receptor at autonomic ganglia (gAChR). Methods Fifty patients were enrolled and divided into two groups according to the presence or absence of gastrointestinal manifestations, and the characteristics were analyzed between these two groups. We measured biomarkers and the autoantibodies against two gAChRα3 and β4 subunits to test sera samples. Furthermore, patients were classified based on the presence or absence of anti-gAChR autoantibodies, and their clinical features were compared. Results In patients with SSc and gastrointestinal manifestations, digital ulcers were more frequent (p = 0.050) and VEGF expression was significantly higher (p = 0.038). Seven subjects with SSc were seropositive for α3 subunit, whereas one patient was seropositive for β4 subunit. The mean level of anti-gAChRα3 autoantibodies in SSc patients with gastrointestinal manifestations was significantly higher than that in SSc patients without gastrointestinal manifestations (p = 0.001). The group of patients with SSc and gAChR autoantibodies had significantly higher endostatin levels (p = 0.046). Conclusions This study is the first to demonstrate that clinical characteristics of SSc patients with seropositivity for gAChR autoantibodies. Patients with SSc have circulating autoantibodies against gAChR, which may contribute to gastrointestinal manifestations associated with this disease, suggesting that gAChR-mediated autonomic neurotransmission may provide a pathomechanism for gastrointestinal dysmotility in SSc.